Food security and climate change - HLPE (Food and Agriculture Organization of the United Nations, 2012)
With many of the resources needed for sustainable food security already stretched, the food security challenges are huge. Climate change will make it even harder to overcome them, as it reduces the productivity of the majority of existing food systems and harms the livelihoods of those already vulnerable to food insecurity. The likelihood of the nations of the world being able to meet the 2°C target of maximal average temperature rise set by the UNFCCC negotiations in Cancun is diminishing with time. If negotiations for global climate policies fail, temperature rises of the order of 4°C by the end of the century, corresponding to the best estimate of the higher emissions scenarios of the IPCC, cannot be discarded. While some might benefit, people in some regions will be affected more than others by changes in average temperature and precipitation. In addition, the likelihood of increased variability and extreme events means that management of risk, both locally and internationally, will be even more important than it is today.